Enhancing Desorption Performance of a Compressible Hybrid Structured Adsorbent via Localized Magnetic Induction Heating - Schoukens, Matthias; Sharma, Ravi; Laha, Priya; Hauffman, Tom; Van Assche, Tom R.C.; Denayer, Joeri F.M. (Advanced materials interfaces, 2024)
Structured adsorbents have gained significant importance in gas separation applications due to their ability to fine‐tune mass and heat transfer and lower pressure drop across the bed. This study presents a ferromagnetic compressible hybrid structured adsorbent, allowing regeneration via magnetic induction heating. A compressible melamine sponge is coated with the CO2‐selective Ni‐MOF‐74 adsorbent and Fe3O4 as a ferromagnetic susceptor, capable of dissipating heat instantaneously in an alternating electromagnetic field. Taking advantage of these properties, the potential of rapid CO2 capture and thermal regeneration via magnetic induction swing adsorption is investigated. The successful incorporation of both ingredients on the melamine sponge is confirmed via SEM‐EDX and XRD analysis. Breakthrough experiments with a CO2/CH4‐mixture are performed. The selective property of Ni‐MOF‐74 toward CO2 is retained, with the composite showing a capacity of 1.89 mmol CO2/g. The compressible nature of the melamine sponge allowed for an improvement of 79% in the volumetric capacity of the adsorbent bed and a higher heating rate. In regard to regeneration, within 1 min of subjecting the structured composite to the alternating magnetic field, an efficient desorption (>90%) of CO2 is achieved. Overall, a ferromagnetic compressible hybrid structured adsorbent is presented for fast cyclic gas‐phase separation processes. Discover an innovative gas separation technique using a ferromagnetic compressible hybrid structured adsorbent. This magnetic sponge combines a CO2‐selective adsorbent (Ni‐MOF‐74) with a magnetic susceptor (Fe3O4) for regeneration via magnetic induction heating. Rapid CO2 desorption (>90%) is achieved within a minute, presenting a promising approach for fast cyclic gas‐phase separation. Compression of the coated sponge further improves the separation performance.